The Utility Model Relates to a Structure Design of a Drawbar Trolley with a Telescopic Stool - Wu, Xinyu; Wang, Tingrui; Zhang, Shengnan; Wu, Shenghong (International Journal of Mechanical and Electrical Engineering, 2024)
As a convenient handling tool, the pull rod car can use people’s pushing and pulling to easily carry heavy objects, achieve the handling tasks that people need to complete, and reduce the burden on the shoulders and arms. The use of a trolley can reduce people’s physical consumption, avoid overwork, especially suitable for long walks or need to carry a large number of items. Its biggest advantage is that it can complete different handling tasks through simple operations, so as to help people easily move items. The main design task of this paper is to transform the traditional draw-bar car, so that it has the function of telescopic stool and upstairs power. The design aims to solve the problem of carrying items and needing rest during shopping, providing a more convenient shopping experience. The specific design idea is to take the stool as the main body, and the shopping cart becomes its auxiliary function; The slider is used as a telescopic mechanism to realize the smooth expansion and contraction of the stool; Add the upstairs power function to drive the shopping cart upstairs through the motor and remote control. In terms of technical implementation, the base is welded with steel, the stool is made of high-strength polymer materials, and the telescopic mechanism is made of sliders. This paper mainly uses UG to carry out 3D modeling.